The role of the community nurse on health committees - V M Taylor; E J Gross; S D Roos (AOSIS, 2001)
With the changes in health care occurring in South Africa, new functions concerning the community nurse are being presented. The goal of the study was to explore and describe the role of the community nurse in health committees. An explorative, descriptive design was used and the empirical part was undertaken within the context of a metropolitan local authority. After conducting a literature study, six major roles of the community nurse on health committees were identified. After that a questionnaire was presented to community nurses to explore and describe their perceptions about the role of the community nurse on health committees. An interview schedule based on the literature study was drafted for presentation to selected members of health committees. Lastly guidelines describing the role of the community nurse on health committees were developed based on the findings of the study.